Kegiatan Pengenalan Kehidupan Kampus FKIP UPI YPTK Goes to School - Afnesha Noveriana Chang; Rahma Dania (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This activity was held by Putra Indonesia University "YPTK" Padang lecturer team to introduce campus life at FKIP UPI YPTK Padang to high school students in Padang. This activity aims to provide an overview of campus life, both academic and non-academic, to high school students in Padang City who wish to continue their studies to a higher level. This activity was also carried out as an effort to increase awareness and interest of students in Padang to continue their education at the FKIP UPI YPTK Padang campus. Apart from that, it is hoped that this activity will provide an overview of the major that will be taken after graduating from high school as well as the job opportunities that can be obtained after completing undergraduate education in the chosen major. The service is carried out by direct visits to schools where the service team explains the choice of majors, study programs and facilities that students can get when continuing their studies at the FKIP UPI YPTK Padang campus.